"A child who is hidden has no rights": Responses to violence against children with disabilities. (March 2019) - Njelesani, Janet
Abstract: Background: There is an urgent need to understand how best to prevent and respond to violence against children with disabilities as they are at a high risk for violence because they are marginalized, isolated, and targeted and have little power within their communities. Objective: Guided by social-ecological theory, this study explores responses to violence against children with disabilities, including preventative measures and treatment of victims in the West African countries of Guinea, Niger, Sierra Leone, and Togo. Participants: Participants were recruited using purposive and snowball sampling from the following three groups: disability stakeholders including representatives from local, national, and international organizations and governments; community members including parents, teachers, and leaders; and children with disabilities. Methods: A qualitative study design guided data generation, that included document analysis, semi-structured interviews, and focus groups across the four countries. In total, 419 people participated. Of those participants, 191 took part in an interview and the rest participated in one of 55 focus groups. Findings: Responses to disability-based violence are driven at the mesosystem and exosystem levels. Prevailing views indicated that national level policies and laws are not always considered part of solutions, communities are leading responses to violence, and children with disabilities are hidden at home or in institutions for both their own and their family's safety. Conclusions The findings can inform development of prevention and intervention programs that will protect children with disabilities from violence in contexts with high levels of disability stigma, social conflict, violence, and poverty.